Study on Possible Existence of Superluminal Photons inside Microtubules and the Resulting Explanation for Brain Mechanism - Musha, Takaaki (Newest Updates in Physical Science Research Vol. 11, 2021)
D.Georgiev presented an idea that consciousness could be the result of quantum computation via short laser-like pulses controlling quantum gates within the brain cortex. However, he later rejected this theory because the wavelength of super radiant photon emission in the infrared spectrum is two orders of magnitude longer than the size of any microtubule cavity. But recent theoretical studies suggested the possibility that the human brain functions by using photons generated inside brain's microtubules, behaving as quantum waveguides or resonant cavities for these photons, which shows how to use them to manipulate quantum bits in microtubules. To revive this idea of quantum computation within the brain, the author proposes that the substance within a microtubule cylinder has characteristics of a metamaterial composed of sub-wavelength structures. From this hypothesis, we can show that microtubule could be used for manipulation of qubits to achieve quantum computation by utilizing superluminal photons, which also permit the microtubule to manipulate the storage and retrieval of stored data in the brain. From which, we can also provide a mechanism for general anesthetic action which brings about a loss of consciousness.